Socioeconomic background, nonverbal IQ and school absence affects the development of vocabulary and reading comprehension in children living in severe poverty. Issue 5 (14th June 2019) - Lervåg, Arne; Dolean, Dacian; Tincas, Ioana; Melby‐Lervåg, Monica
Abstract: Few studies have examined how socioeconomic status (SES) affects two essential parts of human development, namely vocabulary and reading comprehension, in children facing severe poverty. The Roma population is the largest minority group in Europe, the majority of whom live in severe poverty. This study compared the development of 322 Roma children with the development of 178 non‐Roma children, between the ages of 7 and 10 years, living in Romania. The Roma children had poorer initial vocabulary and reading comprehension skills as well as slower growth rates for both compared to the non‐Roma children. Importantly, SES had a direct influence on growth in both reading comprehension and vocabulary. The effect of SES was partly mediated by school absence and nonverbal IQ. This is a powerful finding since it suggests that poverty may have detrimental effects not only on reading but also on the development of verbal abilities. Abstract : Roma children living in poverty has lower initial vocabulary and reading comprehension skills and slower growth in both compared to the non‐Roma children. SES has a direct effect on growth in both reading comprehension and vocabulary. This effect of SES is partly mediated by school absence and nonverbal IQ.